Contenidos virtuales y su influencia en la conducta de los estudiantes de La Unidad Educativa Víctor Emilio Estrada, del cantón Vinces - Quinto Suarez, Claribel del Carmen (2021)
This project whose title is "Virtual content and its influence on the behavior of the students of the Víctor Emilio Estrada Educational Unit" was carried out in order to identify the behavior that students have had as a result of the virtual content that teachers of the institution hang on the digital platforms so that the student has reading material and the virtual teaching that they currently receive can be complemented due to the absence of classes, for this purpose to carry out a methodology with a qualitative and quantitative approach Where to know the perception of the students, surveys will be applied and also to deepen the attitudes observed by the young people, an interview with semi-structured open questions is carried out with teachers of the institution. The results obtained allowed to identify what has been the behavior of young people in the face of virtual contents where it can also be identified the deficiencies that some students may present due to not having technological equipment or access to the internet, it is rescued that teachers have been prepared for the creation of virtual contents to complement the teaching given in the synchronous and asynchronous classes, the students are happy with the contents that are uploaded on their virtual platform.